The effect of hypertension on adult hippocampal neurogenesis in young adult spontaneously hypertensive rats and Dahl rats - Pistikova, A; Brozka, H; Bencze, M; Radostova, D; Vales, K; Stuchlik, A (Physiological research, 2017)
The dentate gyrus of the hippocampus is one of the few places in the brain where neurogenesis occurs in adulthood. Nowadays, an increasing number of children and young adults are affected by hypertension, one of the factors in the development of cerebrovascular diseases and age-related cognitive deficits. Since these cognitive deficits are often hippocampus-dependent, it is possible that hypertension exerts this effect via decreasing adult neurogenesis which has been shown to be essential for a range of cognitive tasks. We used spontaneously hypertensive rats, which develop hypertension in the first weeks of life. Half of them were treated with the antihypertensive drug captopril. We found that the drug-induced lowering of blood pressure in this period did not affect the rate of adult neurogenesis. In a second experiment, we used another animal model of hypertension - salt-sensitive and salt-resistant strains of Dahl rats. A high-salt diet induces hypertension in the salt-sensitive strain, but not in the salt-resistant strain. The high-salt diet led to salt-induced hypertension, but did not affect the level of adult neurogenesis in the dentate gyrus of the hippocampus. We conclude that hypertension does not significantly affect the rate of hippocampal neurogenesis in young adult rats.
Keywords: náhodné rozdělení; Neurogenesis; Hypertension; věkové faktory; krysa rodu Rattus; Hippocampus; zvířata; hipokampus; Rats, Inbred Dahl; krevní tlak; Male; potkani inbrední SHR; hypertenze; Rats; Age Factors; Animals; mužské pohlaví; Blood Pressure; Random Allocation; Rats, Inbred SHR; neurogeneze; potkani inbrední Dahl